Pembagian Harta Bersama Akibat Perceraian (Analisis Perbedaan Pertimbangan Hukum di Mahkamah Syar’iyah Lhoksukon dan Mahkamah Syar’iyah Aceh) - Zuhra Zuhra (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
Mutual property is a property acquired during a marriage outside of a gift or inheritance. In essence, mutual property shall be joint property of husband and wife unless the marriage breaks up as stated in Article 97 KHI that